Simulation and testing of flat rolled aluminum plates 6063 (Nexo Revista Científica, 2011)
An experimental methodology was generated for understanding the theoretical and practical concepts inherent to cold flat rolling. Aluminium slabs about 100 mm length, 9 mm thickness with different widths: 10 and 30 mm were rolled. A constant 0.3 mm thickness reduction step was performed in order to achieve a thickness reduction greater than 80 %. In the Abaqus® commercial software, a mathematical model was implemented in order to obtain a greater understanding concerning how the process variables affect the fields of stresses and strains that are not observed experimentally. It was found, by mathematical simulation, that a superficial hardening in the plates was produced and the deformation obtained is heterogeneous, which is corroborated physically. Keywords: Flat rolling; 6063 Aluminium; Data acquisition system; Simulation DOI: http://dx.doi.org/10.5377/nexo.v24i1.594   Nexo, Vol. 24, No. 1, pp. 50-60, 2011